2018
DOI: 10.1371/journal.pntd.0006918
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy comparison between long-term high-dose praziquantel and surgical therapy for cerebral sparganosis: A multicenter retrospective cohort study

Abstract: BackgroundSparganosis is a parasitic infection caused by the plerocercoid larvae of Spirometra mansoni in East and Southeast Asia. The plerocercoid larvae sometimes invade the encephalon, resulting in severe cerebral sparganosis. Surgical removal of the larvae is considered a standard therapy for cerebral sparganosis. In contrast, the efficacy and safety of long-term, high-dose praziquantel treatment for cerebral sparganosis have not been explored.Methodology/Principal findingsIn this multicenter retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Some authors have declared it as effective as surgical treatment while others have declared it ineffective. A study involving 96 patients showed no signi cant difference between long term high dose praziquantel therapy and surgical treatment (9) . Some patients often require multiple cycles of treatment, and there are still some patients, who cannot be cured with medical treatment (8) .…”
Section: Discussionmentioning
confidence: 98%
“…Some authors have declared it as effective as surgical treatment while others have declared it ineffective. A study involving 96 patients showed no signi cant difference between long term high dose praziquantel therapy and surgical treatment (9) . Some patients often require multiple cycles of treatment, and there are still some patients, who cannot be cured with medical treatment (8) .…”
Section: Discussionmentioning
confidence: 98%
“…Oral medication, including praziquantel, is deemed unable to kill a live worm or achieve beneficial clinical effects [7, 9, 30]. However, recent studies indicated that high-dose praziquantel therapy can be effective in patients with cerebral sparganosis [32, 37, 38]. Of the 15 cases we summarized above, only two patients received oral medication, abendazole and praziquantel, respectively (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, high-dose praziquantel (repeated cycles of 50–75 mg/kg body weight/day for 10 days) has been reported to be effective in inoperable cases of cerebral sparganosis. 13,18…”
Section: Discussionmentioning
confidence: 99%